EVALUASI SISTEM INFORMASI MANAJEMEN DAERAH – BARANG MILIK DAERAH MENGGUNAKAN FRAMEWORK ITIL PADA AREA SERVICE OPERATION DENGAN PENDEKATAN FRAMEWORK CMMI-SVC - I Gede Satya Mulyawan; I Made Candiasa; Dewa Gede Hendra Divayana (SINTECH (Science and Information Technology) Journal, 2022)
In recent years , the Sistem Informasi Manajemen Daerah (SIMDA) – Barang Milik Daerah (BMD) server in Denpasar City had been down several times. These conditions can increase the risk of incidents in service delivery that have not been detected. In this study, an evaluation of SIMDA-BMD was carried out using the Information Technology Infrastructure Library (ITIL) framework version 3 especially the service operation area combined with the Capability Maturity Model Integration for Services (CMMI-SVC) framework with the goal approach. Users and administrators of SIMDA-BMD participated in the assessment as respondents. The questionnaire used a likert scale, then tested for validity and reliability. Technical data were obtained by interviewing the SIMDA-BMD managers. The data was assessed using the capability level of the CMMI-SVC framework. The results is one process area already meeting the target and one process area has one gap level. Recommendations according to the CMMI-SVC framework are prepared based on the requirements for meeting the target capability level. Recommendations in the ITIL framework are carried out through mapping critical success factors and key performance indicators. The resulted is one recommendation from CMMI-SVC framework and six recommendations from ITIL framework that validated using Focus group discussion.